Clinical Effect of Day Surgery in Patients with Lung Caner by Optimize Operating Process. - Yingxian DONG; Daojun ZHU; Guowei CHE; Lunxu LIU; Kun ZHOU; Tao ZHU; Hongsheng MA (Chinese Journal of Lung Cancer, 2020)
Background and objective The types and number of day surgery are increasing, what is the result of day surgery of selected patients with lung cancer? To explore the operation process and clinical effect of day surgery in patients with lung cancer by fusing the concept of enhanced recovery after surgery (ERAS) and minimally invasive surgical techniques. Methods A prospective study was planned with the approval of our institutional review board. 153 lung cancer patients who underwent anatomic resection in a single medical group between June 2019 and Nov 2019 were randomized. 20 patients were applied day surgery and 28 patients by inpatient surgery and the average length of stay, average hospital cost, complications and adverse reactions were analysed. Results The average hospital day in DSG group (1 d) was significantly shorter than in ISG group (7.7±2.8) d (P=0.000). The average hospital cost in DSG group (38,297.3± 3,408.7)¥ was significantly lower than in ISG group (47,831.1±7,376.1)¥ (P=0.000). There was no significant difference in the incidence of postoperative complications between the daytime surgery group (5.0%) and the inpatient surgery group (3.6%) (P=0.812). The postoperation adverse reactions in DSG (10.0%) and ISG (17.9%) is no difference (P=0.72). Conclusion Our study showed that the same clinical effect achieved between DSG and ISG, and recover quickly lung cancer patients after day surgery.